Financial capability among low-income households in rural parts of Poland - Potocki, Tomasz (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2019)
This paper examines low-income households’ financial capability by looking at their financial literacy, financial behaviour as well as financial inclusion. Using the data from micro-study, the author proves that even though financial literacy among low-income households is very low, most financial behaviour (especially the basic ones like managing a financial budget) are rather high. It seems that being financially illiterate does not stop low-income households from being financially capable, which might be mainly connected with some social and environmental factors that shape their capability and help low-income members of households to find some other ways of achieving satisfactory level of financial behaviour than just through increasing financial literacy. Moreover, having little money forces low-income households to become very careful financial decision-makers. Additionally, the multivariate analysis has shown that being financially literate (especially risk and debt literate) and being financially included are key latent factors in understanding financial capability among low-income households from rural regions of Poland. These two factors also play a significant role in understanding the adaptation to low-income among the polled households (measured by the marginal effects of pseudo-R2 ratio in logit model)
Argumenta Oeconomica, 2019, Nr 2 (43), s. 85-114
Keywords: financial capability; financial literacy; personal finance; low-income; financial inclusion; capability approach; poverty; rural regions